PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Konsumen Lipstik Sari Ayu Di Semarang) - Mersha Anjani Putri; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2017)
Competitions among body treatment and cosmetic’s industry had highlyincreased over the time. This escalation could be seen from the outstanding number ofcosmetics either local or international product which revolved in the market. Lipstick wasone of the cosmetic considered to be needed the most by women for their daily activities.Generally, lipstick used by women to make their face looked brighter and avoided palecomplexion. Specifically this research was conducted to analyze the sale of Lipstickproduct from Sari Ayu. It concerned on the problem of insufficient sales of the product inthe last four years. Moreover, in 2014 and 2015 the sales of the lipstick product showed adecline.This research was conducted to analyze how big the influence of the product quality andbrand image toward product repurchase is; by using Sari Ayu’s consumers satisfaction inSemarang as intervening variable. Population of this research was the consumers of SariAyu lipstick in Semarang in which 100 respondents as the sample of the research. Thewriter used purposive sampling as the technique of data collection. Analytical techniqueused in this research was quantitative technique by using OLS multiple regression.The result of this research showed that variable of product quality, brand image andconsumer’s satisfaction influenced repurchase variable either simultaneously or partially.It could be inferred from the multiple regression analysis that variable of product quality(X1) had the most dominant influence.Advice from this research was that Sari Ayu’s company should make an innovation to theproduct (raw material’s innovation) in order to make long-lasting’s lip color. In addition,the innovation in designing the packaging should be considered as well as in advertisingthe product.